PEMANFAATAN SUPERVISI EDUKATIF KOLABORATIF SECARA PERIODIK SEBAGAI UPAYA PENINGKATAN KINERJA GURU SMP NEGERI 3 IBUN DALAM PEMBELAJARAN DI KELAS - Juariah, Ida (STKIP Pesisir Selatan, 2021)
The Purpose of the study is describing the steps of collaborative educative supervision periodically in preparing learning plans, implementing, assessing learning achievement, carrying out follow-up on student learning achievements that can improve teacher performance. This research was carried out at SMP Negeri 3 Ibun, Bandung Regency, starting from supervision on March 7th. until September 2018 This performance improvement is carried out through periodic collaborative educational supervision. The data collection method in this study consisted of four main activities, namely initial data collection, data analysis results at the end of each cycle, as well as other responses from teachers to the implementation of collaborative educational supervision. Based on the results of these studies, it can be concluded that teacher performance increases in preparing lesson plans, implementing learning, assessing learning achievement, carrying out follow-up assessments of student achievement